Cultural adjustment of international students as expatriates in Malaysia - Mohamed, Abdullahi Mohamed (2014)
Expatriates and anyone who goes out of him country where the culture and the environment are different are likely to face culture shock that can affect the performance of the person. This study was carried out in order to find out the type of culture shock faced by international students in Malaysia, the way they adjust the challenges and strategies they use to adapt the host country’ culture. Face to face in-depth interview was conducted with twenty five international students who are currently registered as student in some of the Malaysia’s public universities; the students come from seventeen different countries around the world. The collected data is analysed through qualitative content analyses method. The findings of the study illustrate the type of culture shock faced by international students in Malaysia, the strategies they use to adjust culture shock issues. The study found that the common culture shock that international students in Malaysia face are, language, food, weather and integration with local people.